PENGALAMAN PENGGUNAAN TALKBACK DAN WHATSAPP PADA SMARTPHONE UNTUK MENUNJANG KOMUNIKASI DISABILITAS TUNANETRA - Cut Meutia Karolina; Dwi Ridho Aulianto (Perpustakaan Nasional RI, 2020)
Interaction between one person and another can take place effectively if communication is established in two directions so that messages and information conveyed can be well received and a reciprocal process occurs between one person to another. The communication process happens to everyone, with no exception for people with visual impairments. This study aims to determine the experience of people with visual impairments in communicating with others by utilizing information and communication technology, namely smartphones through the talkback application. Information is taken from the perspective of blind people who experience total blindness and blind people with low vision. The study used a qualitative method with a phenomenological approach, with data collection through in-depth interviews, observation and literature study. Data validity is done through source triangulation techniques. The results of the study concluded that TalkBack is very helpful for people with visual impairments to be able to use smartphones and communicate through WhatsApp applications. It is known that the interpretation of messages received by people with visual impairments is influenced by other factors, for blind people from birth in addition to the role of TalkBack, the touch and audio experience of video messages becomes quite important in interpreting a message and information. In blind people due to accidents, stored memory of experiences of seeing before experiencing blindness is one important part in interpreting messages from WhatsApp, and blind people with low vision conditions, visual vision is very helpful for them in interpreting messages and information received.